(untitled) (Bangladesh Journal of Zoology, 2021)
Drying is one of the common and ancient methods of fish preservation and is generally done in a wide range of open space. This study attempt to evaluate fish drying method at high-rise urban households with three small indigenous fishes namely Mola (Amblypharyngodon mola), Chapila (Gudusia chapra) and Lal Khailsha (Trichogaster lalius). Fishes were dried at high-rise indoor veranda and outdoor rooftop conditions. The dry weight of Mola, Chapila and Lal Khailsha fishes were 70%, 69.5% and 72% in indoor condition and 71.1%, 70.5% and 73% in outdoor condition. The differences of drying capacity between the indoor and outdoor dried fishes were none (p<0.05), thus, the both drying methods are feasible for the urban lifestyle. In dry state, the moisture level in Mola, Chapila and Lal Khailsha were 6.45%, 7.89% and 7.82% whereas, the protein level were 66.51%, 72.26% and 62.02% respectively. The ash value found in the respective fishes was 10.05%, 12.18% and 16.07% and the amount of total fat was 11.14%, 11.28% and 12.32% respectively. The protein and moisture values showed an inverse relationship between the indoor and outdoor condition. The preference analysis of dried fish was found to be highly (100%) accepted among the dry fish-eating consumers from Chittagong, Lakhimpur, Mymensingh, Rangpur, Bandarban, Pabna and Sylhet districts. On the contrary, in case of the consumers of Barisal and Chandpur districts, the level of acceptance was none (0%), whereas the consumers of Kushtia district have accepted the dry fish moderately (60%). Bangladesh J. Zool. 49(1): 117-124, 2021